1998
DOI: 10.1016/s0092-8674(00)81219-2
|View full text |Cite
|
Sign up to set email alerts
|

Histone-like TAFs within the PCAF Histone Acetylase Complex

Abstract: PCAF histone acetylase plays a role in regulation of transcription, cell cycle progression, and differentiation. Here, we show that PCAF is found in a complex consisting of more than 20 distinct polypeptides. Strikingly, some polypeptides are identical to TBP-associated factors (TAFs), which are subunits of TFIID. Like TFIID, histone fold-containing factors are present within the PCAF complex. The histone H3- and H2B-like subunits within the PCAF complex are identical to those within TFIID, namely, hTAF(II)31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
406
0
10

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(432 citation statements)
references
References 50 publications
16
406
0
10
Order By: Relevance
“…Importantly, p53 acetylation was detected in the context of endogenous HAT and endogenous p53 and without use of trichostatin A, a histone deacetylase inhibitor that is commonly added to detect p53 acetylation (Sakaguchi et al, 1998). hAda3 is component of several HAT complexes, including p300/CBP and PCAF, which are recognized p53 acetylases (Gu and Roeder, 1997;Ogryzko et al, 1998;Sakaguchi et al, 1998;Liu et al, 1999a). We demonstrate that p53 acetylation induced by p300 or p14ARF requires hAda3.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Importantly, p53 acetylation was detected in the context of endogenous HAT and endogenous p53 and without use of trichostatin A, a histone deacetylase inhibitor that is commonly added to detect p53 acetylation (Sakaguchi et al, 1998). hAda3 is component of several HAT complexes, including p300/CBP and PCAF, which are recognized p53 acetylases (Gu and Roeder, 1997;Ogryzko et al, 1998;Sakaguchi et al, 1998;Liu et al, 1999a). We demonstrate that p53 acetylation induced by p300 or p14ARF requires hAda3.…”
Section: Discussionmentioning
confidence: 87%
“…Human Ada3 (hAda3) was identified in several HAT complexes (Ogryzko et al, 1998). hAda3 is a 432 amino acid (aa) protein; the N-terminal domain of hAda3 (aa 1-214) binds p53 while the C-terminal domain (aa 215-432) interacts with components of the HAT complex (Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The human lung cDNA library screening by the yeast two-hybrid system using rSGF29 as bait indicated that three out of the 42 b-galactosidase (b-gal)-positive clones encoded hADA3, a component of hGCN5 HAT complexes (Ogryzko et al, 1998). Mapping the domain of rSGF29 responsible for interaction with rADA3 (accession number: BC097414) by the yeast two-hybrid system showed that the coiled-coil domains of rSGF29 (1-105) participate in the association with the rADA3 N-terminal domain (1-214; Figure 4a and b).…”
Section: Resultsmentioning
confidence: 99%
“…A co-factor, TRRAP, which is essential for c-Myc-mediated transformation and interacts with the MbI and MbII domains of the c-Myc, has been identified (McMahon et al, 2000). TRRAP is a part of at least four classes of histone acetyltransferase (HAT) complexes such as SPT3-TAF9-GCN5-acetyltransferase (STAGA) complex, TATA-binding protein-free TAF-containing (TFTC) complex, p300/CBP-associated factor (PCAF) complex and the TIP60-containing complex (Martinez et al, 1998;Ogryzko et al, 1998;Brand et al, 1999;Ikura et al, 2000). c-Myc, through MbI and MbII domains, recruits these HAT complexes, except for TFTC complex, to regulate transcription (McMahon et al, 2000;Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…SAGA (SPT/ADA/GCN5/Acetyltransferase) is a 1.8 MDa complex containing approximately 20 proteins which have been implicated in transcriptional regulation, primarily through genetic screens in yeast (Grant et al, 1997). However, several recent studies have demonstrated that in addition to TRRAP, many other components of the SAGA complex are also highly conserved from yeast to humans (Martinez et al, 1998;Ogryzko et al, 1998;Smith et al, 1998a). Among the many proteins contained in SAGA, the only one with a clearly de®ned biochemical function is the histone acetyltransferase GCN5 (Georgakopoulos and Thireos, 1992;Marcus et al, 1994;Wang et al, 1997).…”
Section: Trrap Links Myc Transactivation To Chromatin Remodeling and mentioning
confidence: 99%